TBLA (TRANSCRIPT BASED LESSON ANALYSIS) UNTUK MENGANALISIS KONSTRUKSI PENGETAHUAN SISWA PADA MATERI BESARAN DAN PENGUKURAN - Rizkika, Rizkika; Susanti, Nova; Rasmi, Dian Pertiwi (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2023)
This research is about how the concept of students' knowledge construction in learning. This research used TBLA (Transcript Based Lesson Analysis) to improve learning at Senior high school 7 Jambi City. The TBLA model provides an analysis for learning input through learning dialog transcripts. The steps in this research are the planning stage (plan), the implementation stage (do), and the reflection stage (see). This research was conducted at Senior high school 7 Jambi City. Constructing students' knowledge during learning is interrogative (Q), asking for opinions, information, suggestions, or assistance. The responsive indicator (A) is answering questions or giving rejection. The suggestive indicator (S) gives suggestions related to the topic of discussion. On the informative indicator (I), which provides information related to the topic of discussion. The exemplification indicator (EX) gives concrete/real examples. On elaborative indicators (EL), namely developing further information, suggestions, or examples. The justification indicator (JT) is an allegation of information, suggestions, or examples.